3D printing of zirconia via digital light processing: optimization of slurry and debinding process. Issue 15 (December 2020) - Sun, Jinxing; Binner, Jon; Bai, Jiaming
Abstract: Digital light processing (DLP) is regarded as one of the most promising 3D printing technologies to process ceramics, however the precise composition of the slurry and the optimisation of the debinding process are still challenges that need to be overcome. In this work, both the dispersion and rheological behaviour of the zirconia slurry were studied using rheometery and UV-vis spectroscopy, and optimising the dispersant concentration was found to have significant benefits. Zirconia green parts were fabricated with zirconia slurry based on DLP technology, which exhibited good dimensional resolution under an exposure energy dose of 15 mJ cm -2 . In addition, the debinding process was studied using TGA and an optimised approach was designed and developed. Dye penetration and SEM results showed that debinding under argon, rather than flowing air, could lead to crack-free parts at heating rates of either 0.2 or 0.5 °C min -1, though the former yielded slightly better results overall.